Further additions to the guardstone spider fauna from China (Araneae: Phrurolithidae) - Mu, Yannan; Zhang, Feng (Zootaxa, 2023)
Twenty-three new phrurolithid species belonging to eight genera, including two new genera, are described from China: Beatitas gen. nov. and Punctus gen. nov., Abdosetae baoting sp. nov., Aculithus brevispina sp. nov., Alboculus yanling sp. nov., Beatitas octomaculatus sp. nov., Otacilia allomanubrium sp. nov., O. guposhan sp. nov., O. horizon sp. nov., O. impleta sp. nov., O. maliu sp. nov., O. shaoyao sp. nov., O. shennongjia sp. nov., O. spina sp. nov., O. striata sp. nov., O. subdentigera sp. nov., O. subforcipata sp. nov., O. wenbi sp. nov., O. yongjia sp. nov., Pennalithus liaoning sp. nov., P. micous sp. nov., Punctus maoxian sp. nov., P. taibai sp. nov., Xilithus pugious sp. nov., and X. wangi sp. nov.. The male of Otacilia ailan Liu et al., 2019 and the female of Grandilithus fengshan Liu & Li, 2022 are described for the first time. Two new combinations, Aculithus pseudofabiformis (Liang et al., 2021) comb. nov. and Corealithus nigerus (Yin, 2012) comb. nov., are established. Corealithus subnigerus (Fu, Chen & Zhang, 2016) syn. n. is also synonymized with C. nigerus comb. nov.. Three species, Otacilia dawushan Liu & Li, 2022 syn. n., O. xingguo Liu & Li, 2022 syn. n. and O. zhonglong Liu & Li, 2022 syn. n., are synonymized with O. wugongshanica Liu, 2020.